Utilitas Aliran Air Sungai Mendukung Potensi Ketahanan Energi (Power Supply) Skala Mikrohidro di Desa Bedadung Kabupaten Jember - Afnani, Fawait; Bahariawan, Amal; Ihsan Alfarizi, Muhammad; Nurhadi, Didik; Zainal Abidin, Ahmad (Universitas Nahdlatul Ulama Sidoarjo, 2025)
Energy shortages remain a major challenge for remote communities, impacting sustainable economic development. Micro-hydropower plants (PLTMH) utilizing flowing water resources offer an efficient and cost-effective renewable energy solution, especially for small-scale electricity needs (<100 kW). a community-based service research project in Bedadung Village, Jember Regency, examined the application of Archimedes screw turbines in PLTMH with variations in the immersion levels of the waterwheel (0.5 and 0.75 of the wheel diameter) and measurements taken at different time intervals. Simulation results showed that a waterwheel immersion of ¾ below the water surface produced an average rotation of 476.27 rpm and a voltage of 12.75 V, which was more optimal for meeting the electricity needs of the local community, particularly in tourist locations and commercial areas. A participatory approach and learning-by-doing methods enhanced community understanding of local resource potential while sustainably building energy and economic self-reliance. This study emphasizes the importance of turbine design adjustments and water resource management for the technical and ecological sustainability of PLTMH in remote areas.